1984
DOI: 10.1083/jcb.98.3.1090
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the expression of the microtubule-associated protein, tau, during mouse brain development, with newly isolated complementary DNA probes.

Abstract: Tau protein is a collection of closely related polypeptides that associate with microtubules in vivo and stimulate their assembly in vitro. Using an affinity-purified antiserum against bovine brain tau protein, we found that the number and amount of tau polypeptides changes dramatically during mouse brain development. The different forms appear to result from changes in tau mRNA since in vitro translation products reflect the qualitative and quantitative changes found in vivo. To study the mRNA and genomic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 31 publications
9
89
0
Order By: Relevance
“…To summarize the results of the PCR analysis of tau transcripts, the comigration of in vitro translation products with natural tau proteins in SDS-gels, and the immunoblots, it was concluded that the four major bovine tau isoforms TI to T4 in their dephosphorylated form are represented by the coding sequences of plasmids pBTA3, 6,8,10,pBTA3,6,8, DISCUSSION Alternative RNA splicing as a means of generating various proteins with altered structures and functions from a single gene is widely distributed in the nervous system (26,41). Transcripts encoding secreted neuropeptides (e.g., substance P and substance K, calcitonin and calcitonin generelated peptide), nerve growth factor, cell surface molecules (N-CAM), structural proteins building the myelin membrane (myelin basic protein and proteolipid protein), and ionchannel components (Shaker locus of Drosophila sp.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize the results of the PCR analysis of tau transcripts, the comigration of in vitro translation products with natural tau proteins in SDS-gels, and the immunoblots, it was concluded that the four major bovine tau isoforms TI to T4 in their dephosphorylated form are represented by the coding sequences of plasmids pBTA3, 6,8,10,pBTA3,6,8, DISCUSSION Alternative RNA splicing as a means of generating various proteins with altered structures and functions from a single gene is widely distributed in the nervous system (26,41). Transcripts encoding secreted neuropeptides (e.g., substance P and substance K, calcitonin and calcitonin generelated peptide), nerve growth factor, cell surface molecules (N-CAM), structural proteins building the myelin membrane (myelin basic protein and proteolipid protein), and ionchannel components (Shaker locus of Drosophila sp.)…”
Section: Resultsmentioning
confidence: 99%
“…While tau proteins and MAP2 are predominantly localized in axons and dentrites, respectively, both are thought to stabilize the microtubule network inside the cell (5,12,17,22). Despite the observed size heterogeneity of tau proteins, previous descriptions of murine (25), human (19), and bovine (21) cDNA clones in addition to immunological data (10,16,23) show that they are highly conserved proteins. The nucleotide sequences of tau cDNAs from different species differ primarily by the insertion and deletion of long nucleotide stretches which maintain the reading frame, which suggests that alternative splicing of tau transcripts could account for the protein heterogeneity.…”
mentioning
confidence: 96%
“…1,2 The synthesis of tau is upregulated along with tubulin during neuronal differentiation; in mature neurons, tau occurs mostly in the axon and is largely excluded from the somatodendritic compartment, whereas other MAPs (e.g., MAP2) predominate in dendrites. 3,4 Microtubules must be able to dynamically grow and shrink, to support cellular shape changes. This is a prerequisite to establishing neuronal polarity and axonal outgrowth.…”
Section: Cell Biology and Function Of Taumentioning
confidence: 99%
“…RNA preparation and Northern blotting. Total cellular RNA was isolated by the LiCI/Urea method (14). Briefly, after rinsing with cold calcium-magnesium free phosphate buffered saline, cells were homogenized in 3 M LiCl and 6 M Urea, and incubated overnight at 4VC.…”
Section: Introductionmentioning
confidence: 99%